Islamic civilisation and the modern world : thematic essays - Bakar, Osman, (UBD Press, 2014)
"This book presents a thematic treatment of Islamic civilisation. Each of the fourteen chapters comprising this book treats at least one of the major themes that are characteristic of this youngest religiously-based civilisation of the world."